Valorization of Heat-Treated Brewers' Spent Grain Through the Identification of Bioactive Phenolics by UPLC-PDA and Evaluation of Their Antioxidant Activities - Rahman, Md. Jiaur; Malunga, Lovemore Nkhata; Eskin, Michael; Eck, Peter; Thandapilly, Sijo Joseph; Thiyam-Hollander, Usha (Frontiers in Nutrition, 2021)
Thermal processing not only disrupts cell membranes and cell walls, but also cleaves covalent bonds releasing low molecular phenolic. This study examined the impact of various heat treatments (100, 140, and 160°C) on the composition of phenolic acids and antioxidant activities in extracts obtained from defatted brewers spent grain (BSG) meal. Heating BSG at 160°C resulted in a 2-fold increase in total phenolic content [TPC, 172.98 ± 7.3 mg Gallic acid equivalent (GAE)/100 g defatted meal] and total flavonoid content [TFC, 16.15 ± 2.22 catechin equivalents (CE)/100 g defatted meal] compared to the untreated BSG extracts. The antioxidant activities of treated BSG extracts, determined by radical scavenging and ferric reducing antioxidant power (FRAP) were significantly (p < 0.5) higher than the corresponding untreated BSG extracts. Eleven phenolic acids were identified and quantified in BSG extracts by Ultra Performance Liquid Chromatography with Photodiode Array (UPLC-PDA). The amounts varied significantly (p < 0.05) depending on the degree of toasting BSG was subjected to. Chlorogenic acid, an ester of caffeic and quinic acid was the predominant phenolic acid present in all fractions. Significant (p < 0.05) increases in TPC, TFC, individual phenolic acids and antioxidant activity were observed in BSG extracts exposed to increasing oven temperatures. These results confirm the ability of heat processing to release bioactive phenolic from their bound forms thereby enhancing the phenolic acids and the digestibility of BSG meal in the intestinal tract.